Clinical characteristics and outcomes of veterans hospitalised with purulent soft tissue infections with and without systemic signs of infection. Issue 7 (2nd July 2016) - Gunderson, Craig G.; Holleck, Jurgen; Chang, John J.; Lin, Shin; Merchant, Naseema; Gupta, Shaili
Abstract: Objective To describe the frequency of systemic inflammatory response syndrome (SIRS) criteria in a cohort of patients hospitalised with purulent soft tissue infections and to determine their impact on clinical characteristics, microbiology and outcomes.Methods Retrospective cohort study of adults hospitalised at the West Haven Veteran's Hospital with purulent soft tissue infections between 1 October 2008 and 30 September 2013.Results A total of 173 patients were included with purulent soft tissue infections; 60 patients had no SIRS, 48 had one SIRS and 65 had ≥ 2 SIRS. Most clinical characteristics were similar between the different SIRS groups, although patients with SIRS were more likely to have severe sepsis and acute kidney injury and to already be on antibiotics at the time of hospitalisation. The microbiology of the infections was similar between SIRS groups. All patients received parenteral antibiotics when admitted and the majority of patients in all SIRS categories received antibiotics with broad Gram-negative activity. Outcomes were generally benign for all SIRS groups, although patients with SIRS had a longer length of stay and a trend towards more bacteremia.Conclusions SIRS are common in patients hospitalised with purulent soft tissue infections, although one third had no systemic signs of infection. Severe sepsis and septic shock are rare. Clinical characteristics, microbiology and antibiotic use are similar among patients in different SIRS groups, although the group without SIRS had a shorter hospitalisation and no episodes of bacteremia. Over-use of antibiotics is common in all SIRS categories.